A study of indicators of fragility in the Iraqi economy - causes and solutions for the period (2006-2022) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Iraq is facing an increasing state of political and economic instability, increasing social unrest, and a deepening gap between the state and the citizen. Nearly two decades after the 2003 war, the country is still stuck in a state of fragility at significant levels, and in the absence of structural reforms in the real sector, Fragility and its many causes are a real obstacle to the Iraqi economy’s ability to absorb the potential for growth and stability. The research aims to explain the reality of fragility in the Iraqi economy, while diagnosing the weak points in the economic structure, leading to presenting the reasons that cast their shadow on the structure of the economy, and explaining the solutions. The researcher concluded that the fragility indicators record sophisticated and advanced positions, and the state’s status is still registered between warning and high alert, as we note that Iraq’s international ranking is among (178) countries, topping the list of fragility indicators, as Iraq registered in (2007) the second fragile state after Sudan, which occupies first place. The researcher recommends the need to work on developing thoughtful plans and strategies towards an economy less dependent on oil, activating the diversification of economic sectors, improving the business environment and investment climate, increasing the transparency of starting businesses and creating new investments, with the need to move towards rebuilding the private sector, and the need for the government to move towards investing and providing full protection for energies. And national minds and eliminating the phenomenon of financial and administrative corruption, while developing a government strategy that strictly ensures the prevention of external interference in Iraqi affairs and a serious move towards imposing the sovereignty and prestige of the state.